The performance of divisia monetary aggregates in the monetary model of exchange rate in ASEAN-four countries - Leong, Choi Meng (Universiti Malaysia Sarawak, (UNIMAS), 2015)
The search for valid exchange rate models has long been one of the main activities in international economics and finance, as the empirical performance of the dominant monetary exchange rate model still remains indefinable. The weak performance of the model is still a puzzle in the literature. Thus, this study continues the effort to improve the performance of the monetary exchange rate model via the investigation of the long-run validity of various monetary models. One of the reasons for the failure of the monetary model is the instability of money demand. The instability of money demand may be due to the use of simple sum money in the estimation of money demand. Thus, the Divisia monetary aggregates are employed to serve as an alternative money measure for the monetary exchange rate model estimates in this study. Besides that, a model misspecification problem may prevail if important macroeconomic variables are not included in the estimates of the monetary models. Therefore, a modified monetary model that incorporates the real stock prices differential is included in the estimates of this study in addition to the flexible-price monetary model (Bilson, 1978 and Frenkel, 1976) and the sticky-price monetary model (Dornbusch, 1976). All of the monetary models are estimated using the autoregressive distributed lag (ARDL) approach to cointegration for Indonesia, Malaysia, the Philippines and Singapore. Based on the results, long-run relationships exist between monetary fundamentals and the exchange rate for Indonesia, Malaysia, the Philippines and Singapore. However, parsimonious models are only found in Malaysia, the Philippines and Singapore. Monetary fundamentals are insignificant in affecting the exchange rate of Indonesia although long-run relationships are found between the variables. For Malaysia, the parsimonious model is the sticky-price monetary model. On the other hand, the flexible-price monetary model is appropriate for the Philippines. The modified monetary model is superior in explaining the exchange rate behaviour for Singapore and it is found that the substitution effect presents in Singapore from the stock prices to the exchange rate. Superior performance of the Divisia monetary aggregates are found in Malaysia and the Philippines. Conversely, the Divisia monetary aggregates are inferior to simple sum money in Singapore. As long-run relationships prevailed in the estimated monetary models, the out-of-sample forecasting continued to identify the forecast performance of monetary models and the random walk model. Monetary models generally predict better in a longer forecast horizon, which is in Indonesia and the Philippines. The monetary model beats the random walk model across all forecast horizons in the case of Singapore. For Malaysia, the monetary model fails to beat the random walk model for all forecast horizons. Generally, this study sheds light on the value of monetary targeting for monetary policy. Furthermore, the exchange rate channel can be revised to serve as a significant transmission mechanism for monetary policy.